1996
DOI: 10.1021/ic960349g
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Characterization, and Molecular Mechanics Calculations of Optically Active Silatrane Derivatives

Abstract: A series of optically active silatrane derivatives, [Si{N(CHRCH(2)O)(CH(2)CH(2)O)(2)}X] (R = Me, i-Pr; X = Ph, OMe) has been synthesized by the reaction of optically active triethanolamine derivatives with XSi(OMe)(3), and characterized by (1)H NMR, (13)C NMR, (29)Si NMR, and mass spectroscopy, and the structures of six compounds have been determined by X-ray analysis. Molecular mechanics methods have also been employed to obtain the energy-minimized structures. The (29)Si NMR chemical shifts and the lengths o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The results obtained from each atom are in concordance with the usual ones for similar chemical connectivities. A relationship between the chemical shift of the atoms X(Y) and the associated X/Y interaction has not been found, although some authors [ [13]] have found linear relationships between the 29 Si NMR chemical shifts (ppm) and the Si/N distances (Å) in the case of derivatives of general formula 99, but they correspond to the perturbation of a [3.3.3]trioxasilatrane by substituents R and X.…”
Section: Nmr Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained from each atom are in concordance with the usual ones for similar chemical connectivities. A relationship between the chemical shift of the atoms X(Y) and the associated X/Y interaction has not been found, although some authors [ [13]] have found linear relationships between the 29 Si NMR chemical shifts (ppm) and the Si/N distances (Å) in the case of derivatives of general formula 99, but they correspond to the perturbation of a [3.3.3]trioxasilatrane by substituents R and X.…”
Section: Nmr Propertiesmentioning
confidence: 99%
“…Note that we called saturated atranes those where their X and Y atoms are connected by carbon atoms exclusively. We will not discuss the D and L stereochemistry of atranes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Use of H 2 PtCl 6 as a catalyst favors transetherification of the two triethoxysilanes as shown by the increased silatrane yields 50 . Organyltriethoxysilanes react with racemic 59 or optically active triethanolamine derivatives 60,61 to afford 4-substituted 1-organylsilatranes (equation 8).…”
Section: Formation From Organyltrialkoxysilanesmentioning
confidence: 99%
“…Silatranes and their tricyclic analogs 1453 substituted silatranes are formed in a similar way 62 . Reaction 2 can also be applied to the synthesis of a number of 1-alkoxy-1,53,61 and 1-aryloxysilatranes 33,63 as illustrated by equations 9 61 …”
Section: Formation From Organyltrialkoxysilanesmentioning
confidence: 99%
See 1 more Smart Citation